Design Of Legal Aid Consultation Service System In One Of The Law Firm In Bandung - Jenny Nurdianti; Dheni Apriantsani Budiman (LPPM STMIK Mardira Indonesia, 2025)
Law practice in Bandung provides professional legal consultation services characterized by high competence and integrity. It aspires to establish itself as a reliable law firm for both Indonesian and foreign populations, addressing their needs and concerns. This law firm in Bandung encounters the issue of insufficient online access to legal service information, necessitating clients to visit the office for consultations. Moreover, the scheduling of consultations and payment processing remain manual, rendering the procedure laborious and inefficient. An alternative option is presented to address these difficulties by deploying a dependable computerized system. This study seeks to establish a legal consultation service utilizing Information Technology (IT). The system is web-based, developed using the PHP programming language with the CodeIgniter 3 framework, and utilizes MySQL as its database management system. The author utilizes Object-Oriented Analysis Design (OOAD) in this research methodology.